Baby-Led Weaning. Issue 6 (November 2016) - Beal, Judy A.
Abstract : Baby-led weaning (BLW) is growing in popularity among parents. This method of introducing solid food is different from the recommendations from the American Academy of Pediatrics. Instead of limiting intake for the first six months to breastmilk or formula and liquids other than milk, small portions of solid food are offered to babies when parents feel their baby is ready. The process of initiating feeding starting with pureed foods spoon-fed to babies by an adult is not part of the baby-led weaning feeding method. Available data on BLW are limited about risks, benefits, and outcomes. Our expert in pediatric nursing, Dr. Beal, explains BLW.